Cellulosic material obtained from Antarctic algae biomass - Paniz, Oscar G.; Pereira, Claudio M. P.; Pacheco, Bruna S.; Wolke, Silvana; Maron, Guilherme K.; Mansilla, Andres; Colepicolo, Pio; Orlandi, Marcelo O. [UNESP]; Osorio, Alice G.; Carreno, Neftali L. (Springer, 2019)
Algae biomass is a raw material widely used by many industrial sectors, such as food production, pharmaceuticals, cosmetics, fertilizers, biofuels, and many others. Its usage is mainly due to the phycocolloids content, such as alginates, carrageenans, agar, etc. One of the polysaccharides present in this biomass, and still little explored is cellulose, an important resource with several technological applications, for example: production of nanocellulose, ultralightweight structures, drug delivery, tissue engineering, wound dressings, among others. Thus, we used the Antarctic algae Cystosphaera jacquinottii as raw material for the production of a cellulosic material combining alkaline treatment, bleaching, and freeze-drying. Fourier-transform infrared spectroscopy results revealed that the methodology employed was effective to obtain cellulose. X-ray diffraction analysis showed that the material obtained had crystallinity above 70%. Scanning electron microscopy analyses showed a highly porous morphology, consisting of cellulose nanofibers with a diameter about 32 nm. [GRAPHICS] .
Keywords: Cellulose; Algae biomass; Cystosphaera jacquinottii